Populärkulturforschung Eine Einführung - Maase, Kaspar (Edition Kulturwissenschaft, 2019)
Popular entertainment and entertainment are considered essentially aesthetic phenomena. But is there a specific "aesthetics of the popular"? And how can mass arts affect the development of worldviews and identity orientations in a problematic way? Kaspar Maase focuses on the "mainstream" of mass arts and their everyday usage practices. In his study, he develops an understanding of popular culture as a network of practical interactions between people, texts, things, contexts, and situations, thus providing basic orientations for empirical research in a variety of disciplines.